EVALUASI PERANGKAT LUNAK SIMULASI MONTE CARLO UNTUK PENENTUAN CADANGAN AWAL DAN ANALISIS RESIKO EKSPLORASI RESERVOIR X, Y, Z, CIREBON JAWA - BARAT - Marwanza, Irfan
In the world of mining, especially in the exploration activity of oil company always faced on the choice to receive or to refuse the offer of exploration and development activity. This case accords with the concept of gambler's ruin validated in each exploration works. Generally each exploration activity has a large risk and the uncertain result. To determine the best choices, the exploration company can use the risk analysis methodology. In this thesis, we apply the risk analysis methodology in the oil exploration with limited exploration data. One method of risk analysis is the simulation technique, namely the method that enables to analyze the possibility to make the risk description and uncertainty in the possible value distribution form. Parameter calculated is the oil reserve and geological risk factor. Prospect of oil reservoir analyzed in this thesis is three reservoir x, y and z in the area of Cirebon, West Java. From the calculation of reserve and risk analysis are found that the result of the smallest risk of the field is the reservoir z, x, and y respectively. Based on the calculation result of volumetric methodology, which also performed to test the simulation analysis result of montecarlo, it is found that the result of calculation by these methods has the close number. It can be concluded that Montecarlo simulation method can be applied if the reservoir with very limited data.